Risk factors and short-term outcomes of postoperative pulmonary complications after VATS lobectomy - Agostini, Paula J. (J Cardiothorac Surg, 2018)
BACKGROUND: Postoperative pulmonary complications (PPCs) are associated with poor outcomes following thoracotomy and lung resection. Video-assisted thoracoscopic surgery (VATS) for lobectomy is now frequently utilised as an alternative to thoracotomy, however patients remain at risk for development of PPC. There is little known of the short-term outcome associated with PPC following VATS lobectomy and if there are any potential risk factors that could be modified to prevent PPC development; our study aimed to investigate this. METHODS: A prospective observational study of consecutive patients undergoing VATS lobectomy for lung cancer over a 4-year period in a regional centre was performed (2012–2016). Exclusion criteria included re-do VATS or surgery for pulmonary infection. All patients received physiotherapy as necessary from postoperative day 1 (POD1) and PPC was determined using the Melbourne Group Scale. Outcomes included hospital LOS, intensive therapy unit (ITU) admission and hospital mortality. RESULTS: Of the 285 patients included in the study, 137 were male (48.1%), the median (IQR) age was 69 (13) years and the mean (±SD) FEV(1)% predicted was 87% (±19). Patients that developed a PPC (n = 21; 7.4%) had a significantly longer hospital LOS (4 vs. 3 days), higher frequency of ITU admission (23.8% vs. 0.5%) and higher hospital mortality (14.3% vs. 0%) (p < 0.001). PPC patients also required more physiotherapy contacts/time, emergency call-outs and specific pulmonary therapy (p < 0.05). Current smoking and COPD diagnosis were significantly associated with development of PPC on univariate analysis (p < 0.05), however only current smoking was a significant independent risk factor on multivariate analysis (p = 0.015). CONCLUSIONS: Patients undergoing VATS lobectomy remain at risk of developing a PPC, which is associated with an increase in physiotherapy requirements and a worse short-term morbidity and mortality. Current smoking is the only independent risk factor for PPC after VATS lobectomy, thus vigorous addressing of preoperative smoking cessation is urgently needed.